Everyday mysticism : a contemplative community at work in the desert - Glucklich, Ariel (New Haven : Yale University Press, 2017)
A scholar's experiences inside a contemplative working community in Israel's Negev desert.
IndexA; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Vendor-supplied metadata.
Includes bibliographical references (pages 241-249) and index.
In English.
JSTOR
Keywords: Neot Smadar (Religious community); Mysticism -- Israel; Mysticisme -- Israël.; BODY, MIND & SPIRIT -- Inspiration & Personal Growth; BODY, MIND & SPIRIT -- Spirituality -- General; RELIGION -- Christianity -- General; RELIGION -- Devotional; RELIGION -- Spirituality; Mysticism; Israel